Identification of Nuclear Localization Signals in the ORF2 Protein of Porcine Circovirus Type 3 - Mou, Chunxiao (Viruses, 2019)
Porcine circovirus type 3 (PCV3) contains two major open reading frames (ORFs) and the ORF2 gene encodes the major structural capsid protein. In this study, nuclear localization of ORF2 was demonstrated by fluorescence observation and subcellular fractionation assays in ORF2-transfected PK-15 cells. The subcellular localization of truncated ORF2 indicated that the 38 N-terminal amino acids were responsible for the nuclear localization of ORF2. The truncated and site-directed mutagenesis of this domain were constructed, and the results demonstrated that the basic amino acid residues at positions 8–32 were essential for the strict nuclear localization. The basic motifs (8)RRR-R-RRR(16) and (16)RRRHRRR(22) were further shown to be the key functional nucleolar localization signals that guide PCV3 ORF2 into nucleoli. Furthermore, sequence analysis showed that the amino acids of PCV3 nuclear localization signals were highly conserved. Overall, this study provides insight into the biological and functional characteristics of the PCV3 ORF2 protein.